Effect of bone morphology of the tibia plateau on joint line convergence angle in medial open wedge high tibial osteotomy - Junya Itou; Umito Kuwashima; Masafumi Itoh; Ken Okazaki (BMC Musculoskeletal Disorders, 2022)
Abstract Background Change in the joint line convergence angle (JLCA) of the knee after high tibial osteotomy (HTO) is difficult to predict accurately. Given that any change in JLCA is intra-articular, the shape of the articular surface, including the bone morphology of the proximal tibia, may affect the alignment of the knee joint postoperatively. The purpose of this study was to investigate the relationship between the shape of the tibial plateau and postoperative alignment of the knee joint by focusing on changes in JLCA. Methods One hundred and nine knees that underwent HTO were retrospectively reviewed. The shape of the tibial plateau was classified based on the slope of the medial and lateral articular surfaces as depressed, flat (within 3 degrees), or convex (pagoda-like). The relationship between the shape of the tibial plateau and radiological parameters was investigated. Results The shape of the tibial plateau was depressed in 38 knees, flat in 52 knees, and pagoda-like in 19 knees. There was a moderate correlation between the postoperative change in JLCA and the preoperative hip-knee-ankle angle for knees with a pagoda-shaped tibial plateau (r = 0.56) but not for the other two shapes. Conclusions These findings suggest that knees with marked varus deformity before HTO are likely to show more change in JLCA postoperatively if the tibial plateau is pagoda-shaped than if it has a depressed or flat shape. The advantage of focusing on the bone morphology of the proximal tibia is that surgeons can easily perform visual assessment using preoperative radiograph.